A comparative analysis of Singapore and Amsterdam´s smart environment and mobility initiatives - Daalen, Lara Van (2023)
This paper explores Singapore's renowned Smart City model and its potential applicability to a European city. Through a comprehensive analysis of six dimensions, including interviews with industry experts, the study researches the key success factors driving Singapore's Smart City Model. Next, using a data-driven funnel process, Amsterdam was selected as the most suitable European city for comparison. The comparative analysis reveals distinct approaches to Smart City development and identifies mutual learning opportunities.